Spontaneous Rapid Resolution of Acute Epidural Hematoma in Childhood - Ismail Gülşen; Hakan Ak; Enver Sösüncü; Alpaslan Yavuz; Nejmi Kiymaz (Case Reports in Medicine)
Acute epidural hematoma is a critical emergency all around the world, and its aggressive diagnosis and treatment are of vital importance. Emergent surgical evacuation of the hematoma is known as standard management; however, conservative procedures are also used for small ones. Spontaneous rapid resolution of these hematomas has also been reported in eight pediatric cases. Various theories have been proposed to explain the underlying pathophysiology of this resolution. Herein, we are reporting a new pediatric case with spontaneously resolving acute epidural hematoma 12 hours after admission to the emergency room.